Gmotni položaj upokojencev - Papež, Marijan (Delavci in delodajalci, 2017)
The article deals with the economic situation of pensioners. One of the statutory tasks of the Council of the Pension and Disability Insurance Institute is to monitor the economic situation of pensioners and disabled workers. A special chapter in the Institute's Annual Report is devoted to that subject. The major impact on the economic situation of pensioners is clearly that of indexation, which, however, has not been carried out in line with the applicable pension and disability insurance law since 2010. Therefore, much more attention has been paid to the economic situation of pensioners recently, the latter having become worse, primarily due to the absence of indexation. The Amending Act ZPIZ-2C was adopted by the National Assembly on 25th of April 2017. The Law will stipulate the minimum pension amount of 500 % from the 1st of October 2017 for the pensioners who had completed at least 40 years of pension qualifying period and female pension beneficiaries who retired having completed the "prescribed pension qualifying period" in individual periods.
Keywords: pokojnine; Slovenija; socialna varnost; upokojenci